Brand Impact on the Perception of Colours and Archetypes - Duarte, Alexandre; Zuffa, Martina; Ashofteh, Afshin (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This study examines how colour, as a symbolic and emotional medium, aligns with brand archetypes and whether brand identities influence the relationship between archetypes and colour perception. Using Jungian archetype theory, colour psychology, and branding literature, the research investigates how consumers naturally associate colours with archetypes, brands with colours, and brands with archetypes. A cross-sectional survey (N=281) and a three-part experimental design were used. Results show that while consumers consistently associate specific colours with archetypes and tend to link brands with archetypes that match their existing narratives, brands only partially mediate these perceptions. Overall, the findings suggest that although archetypal and brand narratives influence the symbolic interpretation of colours, brands do not strongly modify or mediate these associations. This research provides theoretical insights into the symbolic role of colour in branding and emphasizes the limited influence brands have on unconscious colour–archetype connections.